2017
DOI: 10.4314/sajas.v47i6.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Moringa oleifera</i> (Lam.) pods as feed additive on egg antioxidants, chemical composition and performance of commercial layers

Abstract: The present study was designed to investigate the influence of Moringa oleifera (Lam.) pod meal (MPM) on production, immunity, and functional food index of chicken eggs. Two hundred HyLine W36 layer birds aged 50 weeks, 1469 ± 46.63 g, were assigned to four treatments in a completely randomized design, with five replicates and ten birds each. Diets A, B, C, and D were formulated with the same caloric and protein levels, but with differing MPM dose levels of 0, 5, 10, and 15g MPM/kg finisher diet, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 48 publications
2
20
2
1
Order By: Relevance
“…This subsequently leads to a deficiency of amino acids, which leads to a decrease in animal weight and growth (Akinmutimi & Okwu, 2006). Contrary to the results found by the above researchers, Ahmed et al (2017) found Moringa oleifera seed pod meal to have no effect on FI. Similarly, Paguia et al (2014) found the inclusion of Moringa oleifera leaf meal to have no effect on FI.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…This subsequently leads to a deficiency of amino acids, which leads to a decrease in animal weight and growth (Akinmutimi & Okwu, 2006). Contrary to the results found by the above researchers, Ahmed et al (2017) found Moringa oleifera seed pod meal to have no effect on FI. Similarly, Paguia et al (2014) found the inclusion of Moringa oleifera leaf meal to have no effect on FI.…”
Section: Resultscontrasting
confidence: 99%
“…Results from studies carried out by Tsuzuki et al (2003) and Shi et al (2012) observed that SSM supplementation had no effect on the ROL and this may validate the ANF justification since SSM is low in ANFs like phytic acid and saponins. These results are in line with Ahmed et al (2017) when it was reported that the inclusion of Moringa oleifera pod meal had no effect on the ROL.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations